2011
DOI: 10.1088/0256-307x/28/12/124207
|View full text |Cite
|
Sign up to set email alerts
|

Ghost Imaging Using Orbital Angular Momentum

Abstract: We present a novel encoding scheme in a ghost-imaging system using orbital angular momentum. In the signal arm, object spatial information is encoded as a phase matrix. For an 𝑁 -grey-scale object, different phase matrices, varying from 0 to 𝜋 with increment 𝜋/𝑁 , are used for different greyscales, and then they are modulated to a signal beam by a spatial light modulator. According to the conservation of the orbital angular momentum in the ghost imaging system, these changes will give different coincidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The LG modes are the easiest type of vortex beams to generate in a laboratory setting, and excellent reviews exist on the theoretical explanation of OAM, generation of LG beams, and applications using LG beams [36,37]. An extensive study of the vortex beams has found ample applications in the field of communications and optical imaging, among others [35,[38][39][40][41][42][43][44][45][46]. Compared to the traditional Gaussian beam, the use of vortex beams in an imaging system shows significant improvement in the image quality.…”
Section: Orbital Angular Momentum Of Light and Imaging Using Vortex Bmentioning
confidence: 99%
“…The LG modes are the easiest type of vortex beams to generate in a laboratory setting, and excellent reviews exist on the theoretical explanation of OAM, generation of LG beams, and applications using LG beams [36,37]. An extensive study of the vortex beams has found ample applications in the field of communications and optical imaging, among others [35,[38][39][40][41][42][43][44][45][46]. Compared to the traditional Gaussian beam, the use of vortex beams in an imaging system shows significant improvement in the image quality.…”
Section: Orbital Angular Momentum Of Light and Imaging Using Vortex Bmentioning
confidence: 99%
“…Ghost imaging (GI), also called coincidence imaging or correlated imaging, has attracted much attention recently. [1][2][3][4][5][6][7][8][9][10] In a GI system, the image of an object is retrieved by using two spatially correlated beams, a signal beam and a reference beam. The signal beam after illuminating an object is collected with a bucket detector with no spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with QGI without OAM, HGI has some advantages. HGI provides a convenient method for GI system with phase objects, to enhance the edge contrast of image, to need no background subtraction for the high contrast, to provide the potential to implement GI for multiple grayscale objects [12], [13]. HGI is more severely damaged by turbulence aberration [14] because OAM is encoded in the spatial profile of light beams [15]- [17].…”
Section: Introductionmentioning
confidence: 99%